Small Molecule Inhibitors in Adult High-Grade Glioma: From the Past to the Future - Huang, Wenda; Hao, Zhaonian; Mao, Feng; Guo, Dongsheng (Frontiers in Oncology, 2022)
Abstract Glioblastoma is the most common primary malignant tumor in brain and has a dismal prognosis despite patients accepting standard therapies. Alternation of genes and deregulation of proteins, such as receptor tyrosine kinase, PI3K/Akt, PKC, Ras/Raf/MEK, histone deacetylases, Poly (ADP-Ribose) polymerase (PARP), CDK4/6, branched-chain amino acid transaminase 1 (BCAT1), and Isocitrate dehydrogenase (IDH), play pivotal roles in pathogenesis and progression of glioma. Simultaneously, the abnormalities change cellular biological behavior and microenvironment of tumor cells. The differences between tumor cells and normal tissue become the vulnerability of tumor which can be taken advantage of through targeted therapies. Small molecule inhibitors, as an important part of modern treatment for cancers, have shown significant efficacy in hematologic cancers and some solid tumors. To date, in glioblastoma there were more than 200 clinical trials completed or ongoing, in which trials designers used small molecules as monotherapy or combination regimens to correct the abnormalities. In this review, we summarized the dysfunctional molecular mechanisms, highlighted the outcomes of relevant clinical trials associated with small molecule targeted therapies. Based on the outcomes, the main findings were that small-molecule inhibitors did not bring more benefit to newly diagnosed glioblastoma, but the clinical studies involving progressive glioblastoma usually claimed “noninferiority” compared with historical results. On the other hand, as for the clinical inferiority trial, similar dosing regimens should be avoided in future clinical trials.